PENGARUH RENTABILITAS MODAL SENDIRI, SOLVABILITAS, PROFITABILITAS DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013 - Saleh, Ahmadin; -, Desmiyawati; Anisma, Yuneita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims are to proved the impact of equity rentability, solvability (DER), profitability (ROA) and liquidity (CR) to the dividend policy. The population of this study are the whole manufacturing company that listed at Indonesia’s Stock Exchange on Year 2011-2013 as many as 164 companies. Meanwhile the sample determine used purposive sampling method. The company that meet the cirteria are only 68 companies. To analyze the data was used multiple regression method. According to the study result, equity rentqbility (RMS) has a positive and significant effect to the Dividen Payout Ratio. Debt to Equity Ratio (DER) has a positive and significant effect to the Dividen Payout Ratio). Return on Asset (ROA) has a positive and significant effect to the Dividen Payout Ratio. Current Ratio (CR) has a positive but not significant effect to the Dividen Payout Ratio.Keywords: Equity Rentability, Debt To Equity Ratio, Return On Asset Current Ratio, Dividen Payout Ratio.